Selectivity‐enhancement technique for parallel‐coupled SIR based dual‐band bandpass filter. Issue 3 (29th September 2020) - Li, Daotong; Wang, Ju‐An; Liu, Ying; Chen, Zhen; Yang, Lisheng
Abstract: A selectivity‐enhancement technique is presented for design of parallel‐coupled stepped‐impedance resonator (SIR) based dual‐band bandpass filter (BPF) in this article. The presented dual‐band BPF consists of two short‐circuited coupled lines (SCCLs) and a couple of parallel‐coupled SIRs. Theoretical analysis and numerical simulations on the proposed parallel‐coupled dual‐band BPF and SCCLs are implemented, respectively. Additionally, by loading the two different SCCLs at the input and output ports of the parallel‐coupled dual‐band BPF separately, two transmission zeros can be created beside each passband, which will enhance the skirt selectivity and stopband performances significantly. For demonstration, a dual‐band BPF prototype with the center frequencies of 2.3 and 4.4 GHz is designed, fabricated, and measured. The measurement results agree well with the simulation ones, which verifies the feasibility of the technique.